PENERAPAN NILAI-NILAI TOLERANSI BERAGAMA: (STUDI KASUS LEMBAGA DAKWAH KAMPUS JAMAAH SHALAHUDDIN) - Imam Syaifudin; Yuliana Yuliana (Journal SOSIOLOGI, 2022)
This study was to determine the application of religious tolerance values at the Campus Da'wah Institute. The purpose of this study is to explain related to the application of religious tolerance values at the Campus Da'wah Institute. The qualitative research method is descriptive and uses an inductive analysis approach, namely the research process and understanding based on methods that investigate a social phenomenon. Data collection techniques by observation, interviews, and documentation. The theoretical basis used is the Social Construction Theory. The results showed that in the process of implementing the values of religious tolerance, the Campus Da'wah Institute did not run fully. This depends on the understanding of each member of the Campus Da'wah Institute (LDK), and each member has a different background and a different environment so not all values obtained from the Campus Da'wah Institute can be fully applied. The tolerance value process goes through three stages, namely externalization, objectification, and internalization that take place within it.